Mediation Role of Motivation on Job Satisfaction of Batam Manufacturing Industry’s Employee - Shofiy Shofiyah; Yuli Indah Fajar Dini (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research aims to determine the effect of leadership and compensation on job satisfaction which is mediated by motivation in employees of the Batam City manufacturing industry. The research was carried out using quantitative methods by distributing questionnaires via Google Form, collecting 275 respondents who were used in research and testing data processed using Smart-PLS. Based on research results, job satisfaction among employees is very important in an organization, especially in Batam City, the number of unemployed continues to increase, followed by job satisfaction among employees in Batam City who experience dissatisfaction so that holding demonstrations against companies becomes increasingly stressful because it affects work performance. executed by employees in their performance at the company. This research shows that factors such as leadership, compensation, and motivation have a significant influence on employee job satisfaction in the manufacturing industry in Batam City.